PENDAMPINGAN SERTIFIKASI HALAL PRODUK KACANG TEPUNG RESEP MERTUA DENGAN SKEMA SELF DECLARE DI DESA MANARAP BARU - Rakhmawati, Aneta; Fadhillah, Rizky; Utami, Nadia Puteri; Saputra, Rully Rezki; Pratama, Ramadhani Noor; Effendi, Syafwansyah (UPPM Politeknik Gorontalo, 2024)
Halal certification is one of the important steps to increase competitiveness and consumer confidence in food products. This article describes the process of community service activities through halal certification assistance with a self-declare scheme for Mertua Recipe Flour Nuts products, a micro and small enterprise (MSE) in Manarap Baru Village, Kertak Hanyar District, Banjar Regency, South Kalimantan Province. This community service activity aims to help MSEs to understand and make halal certification independently or self-declare through the Free Halal Certification (Sehati) programme facilitated by BPJPH. The implementation method includes direct assistance by the service team consisting of Entrepreneurial Student Program Participants (PMW) ETU Banjarmasin State Polytechnic in collaboration with the South Kalimantan Sharia Economic Society (MES) Halal Product Process Facilitator (P3H Facilitator) to MSEs. The results of the activity show that MSEs have succeeded in compiling certification documents completely and according to the provisions. The mentoring process and the process of applying for halal certification began on 01 November 2024 and the halal certificate is still in the process of being submitted due to queuing and opening and closing of the SEHATI quota by BPJPH.